Analisa Tingkat Kesehatan Bank Berdasarkan Pendekatan RBBR (Risk Based Bank Rating) Pada PT. Bank SulutGo Periode 2015-2018 - Jek Malensang; Dolina L. Tampi; Wilfried S. Manoppo (JURNAL ADMINISTRASI BISNIS, 2019)
To find out how the bank’s health conditions are valued using the RBBR Risk-Based Bank Rating method at PT. Bank SulutGo Manado. The Bank is the financial institutions that have a major role gather funds from the community in the form of savings and distributing the funds to the community in the form of credit with the purpose of improving the community standard of living. This research uses the factor Risk-Based Bank Rating, Factors risk profile, credit risk using the ratio of Net Performing Loan (NPL), market risk by using a ratio Interest Rate Risk (IRR), and liquidity risk by using the ratio of the Loan to Deposit Ratio (LDR). This study shows that Good Corporate Governance (GCG) factors change in each period because the results of the calculation ratios that exist in these factors indicate developments in 2017 and 2018 in the healthy category means that the company is able to overcome the problems that occurred in previous years. Research on the factor risk profile shows that the bank owned by the local government has the average NPL 0,86%, IRR 205,4 %, LDR 101,09 %. The evaluation comprises ratio ROA and NIM shows the average bank rentabilitas belongs to the local government is very adequate for bank capital. The results of the assessment ratio of the CAR shows the entire predicated very healthy that indicates the bank is able to fulfill the obligation of providing the capital.